ANALISIS FAKTOR RISIKO USIA KEHAMILAN DAN PARITAS TERHADAP KEJADIAN ABORTUS - La Ode Ali Imran Ahmad (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2016)
This article is to determine the risk factors for gestational age and parity with the incidence of abortion in the General Hospital of Southeast Sulawesi province in 2010. Research shows that pregnancy is a risk factor with a value abortion (OR = 9696 19 656 lower limit, upper limit = 39 848) and parity not a risk factor for abortion with the value (OR 0789, lower limit = 0.455, upper limit = 1.370). Results of the analysis showed variable mulitvariat gestational age is a major risk factor with Exp (B) = 18,750 CI 95% = lower limit = 9133, the upper limit = 38 495